2013
DOI: 10.1016/j.cca.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four different equations for calculating LDL-C with eight different direct HDL-C assays

Abstract: Background Low-density lipoprotein-cholesterol (LDL-C) is often calculated (cLDL-C) by the Friedewald equation, which requires high-density lipoprotein-cholesterol (HDL-C) and triglycerides (TG). Because there have been considerable changes in the measurement of HDLC with the introduction of direct assays, several alternative equations have recently been proposed. Methods We compared 4 equations (Friedewald, Vujovic, Chen, and Anandaraja) for cLDL-C, using 8 different direct HDL-C (dHDL-C) methods. LDL-C val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 21 publications
1
31
1
Order By: Relevance
“…However, a subsequent analysis of 597 healthy subjects showed better agreement of the Friedewald formula with a directly measured LDL-C [24]. Another recent study compared four formulae in 164 subjects including those with dyslipidemias and co-morbidities and found that the Friedewald equation had the best overall performance for calculating LDL-C [33].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…However, a subsequent analysis of 597 healthy subjects showed better agreement of the Friedewald formula with a directly measured LDL-C [24]. Another recent study compared four formulae in 164 subjects including those with dyslipidemias and co-morbidities and found that the Friedewald equation had the best overall performance for calculating LDL-C [33].…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, the accuracy of calculated LDL-C can be affected by errors from any of these measurements. The aforementioned study also compared calculated LDL-C formulae with 8 directly measured HDL-C assays using homogenous methods and demonstrated that the optimum equation for calculating LDL-C depends on which direct HDL-C assay is used [33]. It was shown that the Daiichi 2-phase method used in our study to measure HDL-C had the third lowest percentage misclassifications using the Friedewald formula, and the second lowest with the Chen formula in a recent study comparing eight HDL-C assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Friedewald equation uses total cholesterol (TC), HDL cholesterol (HDL-C), and triglycerides (TG) to calculate LDL-C [LDL-C ϭ TC Ϫ HDL-C Ϫ (TG/5)]. Data advocating other LDL-C quantitative methods have suggested that this calculation [termed in this manuscript as Friedewald calculated LDL-C (LDL-C F )] misclassifies cardiovascular risk in many patients, particularly those with hypertriglyceridemia (3)(4)(5)(6). Misclassification has been attributed to the TG/5 ratio used in the Friedewald equation, which represents an estimation of VLDL-C based on the average ratio of TG:cholesterol present in VLDL lipoproteins.…”
mentioning
confidence: 99%